Association between BRAF(V600E) mutation and the clinicopathological features of solitary papillary thyroid microcarcinoma - Lu, Hai-Zhen (Oncol Lett, 2017)
The B-Raf proto-oncogene serine/threonine kinase (BRAF)(V600E) mutation is an important oncogene in the development of papillary thyroid carcinoma (PTC) and has been identified as a risk factor for poor prognosis in patients with PTC. However, whether the BRAF(V600E) mutation is a prognostic marker in patients with solitary papillary thyroid microcarcinoma (sPTMC) has not yet been established. The present study aimed to identify the association between BRAF(V600E) mutation and the clinicopathological features of patients with sPTMC. A total of 108 patients with sPTMC who underwent surgery at the Cancer Institute and Hospital of the Chinese Academy of Medical Sciences between December 2010 and December 2012 were analyzed retrospectively. Exon 15 of the BRAF gene was amplified using the polymerase chain reaction and direct sequencing was performed to detect the BRAF(V600E) mutation. Statistical analysis was subsequently performed using SPSS software (version 16.0). The association between BRAF(V600E) mutation and clinicopathological features of sPTMC was tested with the χ(2) test or Fisher's exact test, as appropriate. There were 27 males and 81 females in the cohort, who were aged between 22 and 66 years old, with an average age of 42 years. The BRAF(V600E) mutation was found in 59 out of 108 (54.6%) patients with sPTMC. The presence of the BRAF(V600E) mutation was demonstrated to be significantly associated with extrathyroidal extension (P=0.019), advanced Tumor-Node-Metastasis stage (P=0.007) and the presence of autoimmune thyroiditis (P=0.010). The BRAF(V600E) mutation was not significantly associated with gender, anatomic location or subtype of sPTMC (P>0.05). In addition, the BRAF(V600E) mutation indicated poor prognosis in patients with sPTMC. These results suggest that the BRAF(V600E) mutation is a risk factor for poor prognosis in patients with sPTMC. This knowledge will aid in the risk stratification and post-operative management of patients with sPTMC.